DETERMINAN PEMILIHAN KANTOR AKUNTAN PUBLIK (KAP) - Febby; Sugi Suhartono (Jurnal Akuntansi, 2020)
Abstract In the process of maximizing the value of the company, a conflict of interest between the manager and the shareholders often arises, which is often called an agency problem. This happens because managers prioritize the opposite interests, ownership does not like the personal interests of managers because what managers do will add costs to the company so that it will cause a decrease in corporate profits. Therefore, companies need a corporate monitoring function through external auditors that are used by company managers to reduce agency problems that arise in the company and reduce fraud in the presentation of the company's financial statements. Therefore, this study discusses the factors that can influence the decisions of public accounting firms such as institutional share ownership, managerial stock ownership, largest shareholding, company size, independent commissioners and leverage. The sample in this study consisted of 135 manufacturing companies. Sampling was done by purposive sampling method. The analytical method used is logistic regression analysis using SPSS 20. The conclusion from the results of the analysis in this study is that the largest shareholding has a positive interest in the selection of a public accounting firm. Keywords: Selection of Public Accounting Firm, Independent Commissioner, Institutional Ownership, Managerial Ownership, Largest Share Ownership, Company Size, Leverage. References: Alfian, N., & Suryansyah, A. (2017). "Pengaruh Efektivitas Komite Audit, Ukuran Perusahaan dan Leverage terhadap Pemilihan Auditor Eksternal." Jurnal Akuntansi Dan Investasi, Vol. 2, No. 2, p. 82–93. Anggraeni, O. L., & Ghofar, A. (2013). "Pengaruh Struktur Kepemilikan Dan Mekanisme Tata Kelola Korporat Terhadap Pemilihan Auditor Eksternal Berkualitas." Arens, A., A., R., J. Elder dan M., S., B. (2014). "Auditing Dan Jasa Assurance", Alih bahasa oleh Heran Wibowo, Jakarta: Penerbit Erlangga Cholifah, A. (2011). "Pengaruh Mekanisme Corporate Governance Terhadap Pemilihan Auditor Eksternal." Jurnal ULTIMA Accounting, Vol. 3, No. 1, p. 46–65. Darmadi, S. (2012). "Ownership Concentration, Family Control, and Auditor Choice: Evidence from an Emerging Market." SSRN Electronic Journal, No. 2, p. 1–42. Dewi, C. I. R. S., & Ratnadi, N. M. D. (2014). "Faktor-Faktor Yang Mempengaruhi Pemilihan Kantor Akuntan Publik Pada Industri Manufaktur Di Bursa Efek Indonesia," E-Jurnal Akuntansi Univesitas Udayana Vol. 8.1, p. 187–199. Dewi, C. I. R. S., Surya, L. P. L. S., & Suindari, N. M. (2019). "Pengaruh Leverage Dan Kepemilikan Institusional Pada Pemilihan Jasa Audit Eksternal (Studi Pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia)" Vol. 18, No. 1, p. 26–32. Eisenhardt, K. M. (1989). "Agency Theory : An Assessment and Review," Vol. 14, No. 1, p. 57–74. Fitriyani, N. M. D., & Erawati, N. M. A. (2016). "Good Corporate Governance Dan Karakteristik Perusahaan Pada Pemilihan Auditor Eksternal." E-Jurnal Akuntansi, Vol. 15, No. 1, p. 229–256. Ghozali, imam. (2016). "Aplikasi Analisis Multivariete Dengan Program IBM SPSS 23" (Edisi 8). Semarang: Universitas Diponegoro. Habeahan, M. S., & Habibi Z, M. R. (2017). "Analisis Mekanisme Corporate Governance dan Tipe Kepemilikan Perusahaan Terhadap Pemilihan Auditor Eksternal." Jurnal Mediasi Unimed, Vol. 6, No. 2, p. 73-93 Jensen, M. C., & Meckling, W. H. (1976). "Theory of The Firm Manajerial Behaviour, Agency Cost and Ownership structure." Journal of Financial Economics, No. 3, p 305–360. Knechel, W. R., Niemi, L., & Sundgren, S. (2008). "Determinants of Auditor Choice: Evidence from a Small Client Market." International Journal of Auditing, Vol. 12, No. 1, p. 65–88. Lennox, C. (2005). "Management ownership and audit firm size." Contemporary Accounting Research, Vol. 22, No.1, p. 205–227. Maharani, D. (2012). "Analisis Mekanisme Corporate Governance Perusahaan Terhadap Pemilihan Auditor Eksternal", p. 1–34. Maharani, D. A., & Pinasti, M. (2018). "Corporate Governance dan Pemilihan Auditor." Vol. 20, No. 3. Markali, O. E., & Rudiawarni, F. A. (2012). "Hubungan Mekanisme Corporate Governance dengan Pemilihan Auditor pada Badan Usaha", Vol. 1, No. 1, p. 1–17. Murhadi, W. R. (2009). "Good Corporate Governance and Earning Management Practices: An Indonesian Cases". Nafasati P, F., & Indudewi, D. (2015). "Pengaruh Mekanisme Internal Corporate Governance Terhadap Pemilihan Auditor Eksternal." Jurnal Dinamika Sosial Budaya, Vol. 17, No. 1. Putra, D. (2014). "Pengaruh Mekanisme Corporate Governance Terhadap Pemilihan Auditor Eksternal." Proseding Seminar Bisnis dan Teknologi. p. 148–159. Republik Indonesia (2008). Peraturan Menteri Keuangan, (2008) "Nomor: 17/PMK.01/2008 Tentang Jasa Akuntan Publik" Rosita, L., Respati, N. W., & Sondakh, A. G. (2015). "Pengaruh Kepemilikan Asing , Komisaris Independen, Efektivitas Komite Audit, Ukuran Perusahaan dan Leveragge Terhadap Pemilihan Auditor Eksternal." Simposium Nasional Akuntansi Vol. XX, No. 2, p. 1–18. Setiawan, A. S., & Karsana, Y. W. (2015). "Faktor Representasi Stock Holder dan Debt Holder Berpengaruh terhadap Keputusan Pemilihan Auditor Berkualitas." Jurnal Akuntansi, Vol. XIX, No. 03, p. 326–339. Trisnawati, I. T. A. (2015). "Faktor Determinan Pemilihan Auditor Eksternal Yang Berkualitas." Jurnal Bisnis Dan Akuntansi, Vol. 17, No. 2, p. 112–124. Zureigat, Q. M. (2011). "The Effect of Ownership Structure on Audit Quality: Evidence from Jordan." International Journal of Business and Social Science, Vol. 2, No. 10, p. 38–46.